Penerapan Metode Discussion-Comparision with Critical Analysis Terhadap Aktivitas dan Hasil Belajar Siswa SMAN 7 Kota Bengkulu - Rosita Fajariah; Irwandi; Mariana Ade Cahaya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to examine the implementation of the Discussion–Comparison with Critical Analysis method among Grade X students of SMA Negeri 7 Bengkulu City in the 2024/2025 academic year. The research employed a quasi-experimental design using a nonrandomized control-group pretest–posttest model, with class X.1 as the experimental group and class X.3 as the control group. The research instruments consisted of observation sheets and multiple-choice tests. The results showed that the learning activity of the experimental class reached 69% (good), which was higher than that of the control class at 49% (fair). The average posttest score of the experimental group was 70.52 with an N-Gain of 0.2779, while the control group obtained an average score of 47.77 with an N-Gain of 0.2015. Statistical testing (p < 0.05) confirmed a significant difference in learning outcomes between the two groups. In conclusion, the Discussion–Comparison with Critical Analysis method was proven to be effective in improving students’ learning activities and learning outcomes. Keywords: learning activities, biology, critical analysis, discussion–comparison, learning outcomes